2021
DOI: 10.1021/acssynbio.1c00361
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Genetic Elements of the Plasmid-Driven T7 System for Stable and Robust One-Step Cloning and Protein Expression in Broad Escherichia coli

Abstract: The plasmid-driven T7 system (PDT7) is a flexible approach to trigger protein overexpression; however, most of the reported PDT7 rely on many auxiliary elements or inducible systems to attenuate the toxicity from the orthogonality of the T7 system, which limits its application as the one-step cloning and protein expression system. In this study, we developed a stable and robust PDT7 via tailoring the genetic elements. By error-prone mutagenesis, a mutated T7RNAP with TTTT insertion conferred a trace but enough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…One of the major concerns in the T7 system is an imbalance regulation between the genetic elements regarding recombinant gene expression. High expression of T7RNAP may cause strong T7 orthogonality in cells and introduce mutations. , The strategy for selecting the T7RNAP integration site should be precise and effective. Due to lac operon being inactive at high glucose concentration, it will decrease the cyclic adenosine monophosphate level and inhibit the trans -glycosylation of lactose into allolactose …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major concerns in the T7 system is an imbalance regulation between the genetic elements regarding recombinant gene expression. High expression of T7RNAP may cause strong T7 orthogonality in cells and introduce mutations. , The strategy for selecting the T7RNAP integration site should be precise and effective. Due to lac operon being inactive at high glucose concentration, it will decrease the cyclic adenosine monophosphate level and inhibit the trans -glycosylation of lactose into allolactose …”
Section: Resultsmentioning
confidence: 99%
“…Hence, fine-tuning of T7RNAP expression was inevitably required to optimize production by varying the genetic elements, including promoter strengthens (e.g.,E. coli,Pseudomonas putida, andSinorhizobium), ribosome engineering, and origin of replications, ,, or the dosage of inducers . Besides that, an alternative approach was to integrate the T7RNAP at different chromosomal loci, which could result in a differential expression.…”
Section: Introductionmentioning
confidence: 99%
“…Since it is an enzyme, the catalytic activity of T7 RNAP is also a key factor affecting the rate and efficiency of transcription. Mutations of key amino acid residues in T7 RNAP are one of the most effective methods to tune its activity, whose mechanisms are divided into two categories: weakening the binding ability to P T7 or generating code-shifting mutations to reduce the catalytic activity [36][37][38]. For example, Baumgarten et al [37] found a single amino acid mutation (A102D) of T7 RNAP in the membrane protein expression host Mt56(DE3), which reduced the ability to bind to the P T7 and decreased the RP production rate.…”
Section: Regulation Of the Target Protein Expression Rate-t7 Rnapmentioning
confidence: 99%
“…Therefore, an appropriate copy number can provide a balance between growth and production. Generally, replicon replacement is a preferred method for regulating copy numbers [38,54], with choices ranging from high-copy-number replicons (pUC series, 500-700 copies [55]) to low-copy-number replicons (pSC101, < 5 copies [56]). However, this permanent adjustment of copy numbers makes it difficult to balance the host burden of high copy numbers or low production due to insufficient plasmid copies.…”
Section: Regulation Of the Target Protein Expression Rate-pet Plasmidmentioning
confidence: 99%